Frederik Kortlandt: Selected Writings on Slavic and General Linguistics: Rodopi, Amsterdam/ New York, NY 2011, 470 pp. - Sukač, Roman (Slavia Centralis, 2020)
The paper presents a book by Frederik Kortlandt, which contains some of his papers on Slavic and general linguistics.